2009
DOI: 10.1007/s11552-009-9225-4
|View full text |Cite
|
Sign up to set email alerts
|

Scratch Collapse Test Localizes Osborne's Band as the Point of Maximal Nerve Compression in Cubital Tunnel Syndrome

Abstract: The objective of this study is to demonstrate the utility of the scratch collapse test (SCT) in localizing the point of maximal compression in cubital tunnel syndrome. From January 1, 2004 to December 1, 2005, 64 adult patients with cubital tunnel syndrome were evaluated by a single surgeon. Cubital tunnel syndrome was diagnosed based upon symptoms of numbness, tingling, and/or pain in the ulnar nerve distribution or by the presence of weakness or wasting of the ulnar-innervated intrinsic hand muscles. All dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
(49 reference statements)
2
25
0
1
Order By: Relevance
“…The use of the SCT has also been suggested as an important tool in differentiating between levels of ulnar nerve entrapment at the level of the elbow [4]. Similarly, SCT was an important adjunct in diagnosing LTS, along with specific muscle weakness and pain at the level of entrapment (lacertus tunnel).…”
Section: Discussionmentioning
confidence: 99%
“…The use of the SCT has also been suggested as an important tool in differentiating between levels of ulnar nerve entrapment at the level of the elbow [4]. Similarly, SCT was an important adjunct in diagnosing LTS, along with specific muscle weakness and pain at the level of entrapment (lacertus tunnel).…”
Section: Discussionmentioning
confidence: 99%
“…The patho-physiology is similar to the carpal tunnel syndrome and similar nerve entrapment on the arm [6]. Brown et al found that the scratch collapse test was a seemingly reliable physical examination technique for localizing the point of maximal nerve compression in patients with cubital tunnel syndrome [7]. The scratch collapse test is simple and rapid to perform and it seems reasonable to add this test to the diagnostic toolbox also for analysis of ankle pain.…”
Section: Discussionmentioning
confidence: 99%
“…Osborne’s ligament has frequently been implicated in the etiology of ulnar neuropathy [4-6,9,16,29]. It has been proven that the cubital tunnel’s volume deep to the ligament decreases as the elbow flexes [2].…”
Section: Reviewmentioning
confidence: 99%
“…For this examination, the patient sits with a flexed elbow at 90 o  and fingers pointing toward the examiner who attempts to rotate the forearm medially and takes note of the patient’s baseline “resistance.” The area over the proposed site of entrapment is then stroked and the test is repeated. An observable decrease in “resistance” indicates a positive test, while simultaneously identifying the site of impingement in the vicinity of Osborne’s ligament [9]. Cheng, et al used the scratch collapse test for diagnosing cubital tunnel syndrome with 89% accuracy [34].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation